Aesthetic practices and politics in media, music, and art: performing migration - Davis, Rocío G.; Fischer-Hornung, Dorothea; Kardux, Johanna C. (Routledge research in cultural and media studies, 2011)
Introduction : Aesthetic practices and politics in media, music, and art / Rocío G. Davis, Dorothea Fischer-Hornung, and Johanna C. Kardux -- Border crossings and (trans)nationalism in film. Paradigms of attitudes towards immigration : science fiction films as allegories in the mid-century / Juan Bruce-Novoa -- No country for old certainties : ambivalence, hybridity, and dangerous crossings in three borderland films / Page Laws -- Bodies and hybrid tropes : border crossings in recent films / Cathy Covell Waegner -- From alien nation to alienation : tracing the figure of the guest worker in Fatih Akin's Gegen die Wand / Tessa C. Lee -- "Lunch with the bigot" : 9/11 in Bollywood's filmic imagination / Mita Banerjee -- Migrant adaptations in television. Invisible ethnicity : Canadian erasure, vanishing Dutchness / Aritha van Herk -- Performing linguistic identity and integration : the politics of interpellation in the Catalonian media / Klaus Zilles -- The trans/migrant in the spotlight : space and movement in Brazilian telenovelas / Gundo Rial y Costas -- Traveling sounds : music and migration. Migratory objects in the Balkans : when the sound of the other sounds strangely familiar / Maria Boletsi -- Variations on a fugitive's song : the performance of disappearance and forced migration in Chile / Nicols Salazar-Sutil -- Immigration and modernism : Arnold Schoenberg and the Los Angeles émigrés / Kenneth H. Marcus -- Performing ethnicity and migration : cultural and artistic practices. Ethnic nostalgia : ethnicity as cultural practice in the twenty-first century / Marcus Embry -- Connoisseurs of urban life : aesthetic practices and the everyday among Japanese migrants in New York City / Olga Kanzaki Sooudi -- "All islands connect under water" : Ping Chong's Undesirable elements series / Roberta De Martini